2016
DOI: 10.18632/oncotarget.7102
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic implications of IL-6/IL-6R/gp130-targeting agents in breast cancer

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine with known multiple functions in immune regulation, inflammation, and oncogenesis. Binding of IL-6 to the IL-6 receptor (IL-6R) induces homodimerization and recruitment of glycoprotein 130 (gp130), which leads to activation of downstream signaling. Emerging evidence suggests that high levels of IL-6 are correlated with poor prognosis in breast cancer patients. IL-6 appears to play a critical role in the growth and metastasis of breast cancer cells, renewal of brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 100 publications
(113 reference statements)
1
93
0
Order By: Relevance
“…(40)(41)(42) Previous papers revealed that IL-6 promotes growth and epithelial-mesenchymal transition of CD133 + cells of nonsmall cell lung cancer, (48) tumorigenicity of oral cancer stem cells, (49) cell adhesion, cancer stem-like and metastatic spread of prostate tumors, (50) the growth and metastasis of breast cancer cells, renewal of breast cancer stem cells (BCSC), and drug resistance of BCSC. (51) Furthermore, it was reported that CD133 + cells produced IL-6, (48) suggesting that cancer stem cells may potentially reduce anti-tumor immunity in vivo.…”
Section: Other Aspects Of Interleukin-6 For Anti-tumor Immunity and Tmentioning
confidence: 99%
“…(40)(41)(42) Previous papers revealed that IL-6 promotes growth and epithelial-mesenchymal transition of CD133 + cells of nonsmall cell lung cancer, (48) tumorigenicity of oral cancer stem cells, (49) cell adhesion, cancer stem-like and metastatic spread of prostate tumors, (50) the growth and metastasis of breast cancer cells, renewal of breast cancer stem cells (BCSC), and drug resistance of BCSC. (51) Furthermore, it was reported that CD133 + cells produced IL-6, (48) suggesting that cancer stem cells may potentially reduce anti-tumor immunity in vivo.…”
Section: Other Aspects Of Interleukin-6 For Anti-tumor Immunity and Tmentioning
confidence: 99%
“…It has been identified to play noteworthy role in anti-inflammatory, hepatoprotective and antiallergic activities. It suppresses cell proliferation of various types of cancer, including multiple myeloma (13), colon (14), breast (15), pancreatic (16) and prostate cancer (17) by inhibiting the STAT3 signaling pathway. It has not been reported previously that UA inhibits phosphorylation of JAK2 and STAT3 in liver cancer cell lines and suppresses growth of hepatocellular carcinoma.…”
Section: Inhibition Of Stat3 Signaling Pathway By Ursolic Acid Supprementioning
confidence: 99%
“…Thus, IL-6 plays a crucial role in the infl ammation-mediated "cancers types", including prostate, breast, gastric, colon, lung and brain due to inducing different cytoplasmic tyrosine kinases and transcription factors and thus, overexpression of IL-6 is associated with poor prognosis in many cancers. Previous studies mentioned that IL-6 mediated STAT3 activation could be a therapeutic target in gastric, glioblastoma, breast, ovarian and lung cancer patients due to mediating muscle wasting (14)(15)(16)(17)(18)(19)(20). However, further studies are still needed to clarify the association between the changes in IL-6 and STAT-3 levels and cancer patients with and without cachexia.…”
Section: Introductionmentioning
confidence: 99%